DESIGNING READING-WRITING TEACHING STRATEGY FOR THE ACADEMIC WRITING COURSE - Anis Firdatul Rochma (Jurnal Bahasa Lingua Scientia, 2023)
The concept of integrating reading and writing in the language instruction has been portrayed through an increasing number of research studies. Nevertheless, many areas remain to be explored. Even though previous research studies often portrayed the beneficial impacts of integrating reading and writing, yet they do not suggest how such impacts affect the students in a specific course. Hence, the present research study aims to propose a design of reading-writing teaching strategy that needs to be addressed within a specific course especially the academic writing course. This research study employed the adapted model of ADDIE (Dick et al., 2015) to develop the proposed teaching strategy. The process of need analysis was carried out through analysing the introduction section of research articles written by the undergraduate students using Swales and Feak’s CARS model (2004) and examining the syllabus of reading and writing courses. Meanwhile, as the primary frameworks for the teaching strategy development, the rhetorical reading strategies and academic writing were adopted. The results of need analysis show that, mostly, undergraduate students’ research articles lack 1 step in Move 1, 2 steps in Move 2, and 3 steps in Move 3 particularly in the introduction section. The omission of steps in the CARS model by these student-authors seems to happen due to two major factors, namely the scarcity of (1) control over the writing process and (2) linguistic resources. Hence, suggesting the reading-writing teaching strategy for academic writing courses is considered essential.